PERAN AGAMA DAN BUDAYA DALAM MEMBENTUK KEPRIBADIAN - Sri Mulyani (AT-THARIQ: Jurnal Studi Islam dan Budaya, 2021)
Humans are social beings at the same time as individual beings. As individual beings, humans have a personality that is different from others. Every individual since childhood has begun to establish a psychological relationship with himself and with his social environment. The existence of individual differences is basically caused by differences between religion and the situation of the cultural environment faced by each. Religion and culture are considered to be one of the factors that can shape a person's personality. This study aims to find out how the role of religion and culture in shaping personality. This research is library research, collecting data using the Documentation method, namely searching for data from a lot of related literature, both printed and electronic, and data analysis using the Content Analysis method, which is analyzing the contents of books that are relevant to the title. The results of the study indicate that the role of religion and culture can shape personality through the application of religious values and socio-cultural interactions that last a lifetime in the family, school and community. Religion and culture will shape a person's personality both as an individual and as a member of society, it is hoped that religion and culture can run properly both in the family, school and community environment.Keywords: Religion, Culture, Personality.